Prevalence of Smoking and Beliefs and Attitude Toward Smoking Habit and Smoking Cessation Methods Among Pharmacy Students: A Cross-Sectional Study in Saudi Arabia - Alwhaibi, Abdulrahman; Wajid, Syed; Alenezi, Ahmad; Salami, Yazeed; Alhaydan, Ibrahim; Samreen, Sana; Alhossan, Abdulaziz; Al-Arifi, Mohamed N. (Frontiers in Public Health, 2022)
Objective The impact of pharmaceutical services on public health especially in regards to smoking cessation counseling can influence the rate of smoking cessation. The present study aims to evaluate prevalence, beliefs, and attitude of pharmacy students toward smoking habit and SC methods. Methods An online cross-sectional survey was conducted among pharmacy students at King Saud University, Riyadh, Saudi Arabia over 4-month period from May to August 2021. The survey consisted of 22-items focused on evaluating the prevalence, belief, and attitude toward smoking habits and smoking cessation methods. Data was descriptively analyzed using a statistical package for social science version 26 (SPSS). Results A total of 675 students completed the survey, among which 78.7 % were non-smokers and only 31.7% received education on the dangers of smoking. The most common methods of smoking cessation they heard of were consultation (58.6%), followed by use of electronic cigarettes (41.92 %) and Nicotine patch (40.7%). One-third of the surveyed students (36.8 %) agreed that specialized smoking cessation clinics enhance the efficacy of smoking cessation methods. The majority of students (80.6%) agreed to ban smoking in public places and 92.2% believed that tobacco sales to adolescents should be forbidden. Health professionals should actively participate and advise their patients to quit smoking as 89.8 % students agreed on that. Age and gender of students had significantly influenced the prevalence of smoking, history of smoking, frequency of smoking, efforts to quit smoking among smokers (p = 0.0001). Conclusion The prevalence of non-smokers among pharmacy students is encouraging, yet level of awareness about and usefulness of smoking cessation methods is unsatisfactory. Therefore, the study clearly highlights a great need for integrating smoking cessation programs in their academic curricula to prepare them for real-world practice.